ANALISIS PUTUSAN PENOLAKAN PEMBATALAN MEREK “PIERRE CARDIN” - Irawan, Vania; Budiningsih, Catharina Ria (Veritas et Justitia, 2023)
Well-known trademarks are crucial to be protected because they are susceptible to infringement by third parties. Disputes concerning well-known trademarks are quite prevalent in Indonesia. One case involving a well-known trademark in Indonesia that is the focus of this research is the "PIERRE CARDIN" trademark case. Therefore, this research aims to investigate and analyze the "PIERRE CARDIN" trademark case based on Decision Number 15/Pdt.Sus-Merek/2015/PN.Niaga.Jkt.Pst, Decision Number 557 K/Pdt.Sus-HKI/2015, and Decision Number 49 PK/Pdt.Sus-HKI/2018. The research methodology employed is descriptive-analytical, involving an examination of legal documents and literature in the field of law. The analysis results indicate that there were inaccuracies in the judge's decision-making. The judge ruled that there was no evidence of bad faith in an individual's registration of the "PIERRE CARDIN" trademark, even though the registered trademark was the same as another individual's name and well-known trademark. The judge also made an inaccurate decision regarding the distinctiveness of the trademark. This inaccuracy in the decision could have implications for trade and investment due to the uncertainty surrounding the enforcement of protection for famous trademarks in Indonesia.